Design of a Growing Media Control System on IoT-Based Vanda Douglas Orchids - Soelistianto, Farida Arinie; Rahmah, Nurul Silviyatur; Dali, Sri Wahyuni (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
In the era of rapid technological development, the need for systems or tools that facilitate daily activities and support human life is becoming increasingly urgent. One application that can assist humans in efficiently controlling their environment is a plant monitoring system. This research implements this concept in the context of agriculture and the environment to monitor the quality of the plant ecosystem through the utilization of smartphones and internet connectivity. By leveraging smartphones equipped with specialized applications, users can easily control and obtain sensor readings. This study employs pH soil sensors, DS18B20, and YL-69 to measure pH, temperature, and humidity values of the growing media. The use of a water pump regulated based on humidity levels is a crucial component of this system. Data generated are processed by NodeMCU ESP32 and sent to smartphones. The results of this research yield a device capable of detecting plant media conditions and controlling watering both automatically and manually. Consequently, users can conveniently monitor the health of their plants. This system holds significant potential for enhancing agricultural efficiency and environmental management through the utilization of digital technology and internet connectivity.